2019
DOI: 10.1093/icvts/ivz210
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve patients show specific epigenetic tissue signature increasing extracellular matrix destruction

Abstract: OBJECTIVES Patients with a bicuspid aortic valve (BAV) have an increased risk for developing thoracic aortic aneurysm, which is characterized by the destruction of the elastic media of the aortic wall. Several important enzymes have been characterized to play key roles in extracellular matrix homeostasis, namely matrix metalloproteinases (MMPs). In this study, we investigated MMP-2 levels and their epigenetic regulation via the miR-29 family. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…By conducting microRNA sequencing of HUVECs under PTH intervention, miR‐29a was shown to inhibit EndMT, and after stimulation of PTH, miR‐29a was observed to be decreased but was restored by PTHR1 inhibitor [PTHrP(7‐34)], indicating that PTH regulated miR‐29a via PTHR1. Meanwhile, in the valves of the CKD rat model, miR‐29a was found to be decreased compared to CTL, which was consistent with previous studies in non‐CKD VC diseases 26‐28 . Besides, the miR‐29a/b cluster was reported to suppress high glucose‐induced EndMT in human retinal microvascular endothelial cells 29 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By conducting microRNA sequencing of HUVECs under PTH intervention, miR‐29a was shown to inhibit EndMT, and after stimulation of PTH, miR‐29a was observed to be decreased but was restored by PTHR1 inhibitor [PTHrP(7‐34)], indicating that PTH regulated miR‐29a via PTHR1. Meanwhile, in the valves of the CKD rat model, miR‐29a was found to be decreased compared to CTL, which was consistent with previous studies in non‐CKD VC diseases 26‐28 . Besides, the miR‐29a/b cluster was reported to suppress high glucose‐induced EndMT in human retinal microvascular endothelial cells 29 .…”
Section: Discussionsupporting
confidence: 88%
“…17 Meanwhile, in the valves of the CKD rat model, miR-29a was found to be decreased compared to CTL, which was consistent with previous studies in non-CKD VC diseases. [26][27][28] Besides, the miR-29a/b cluster was reported to suppress high glucose-induced EndMT in human retinal microvascular endothelial cells. 29 In this study, overexpression of miR-29a was shown to inhibit PTH-induced EndMT in the valves of CKD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of metalloproteinase (MMP) gene expression is associated with valvopathies. An increase in MMP‐2 was observed in patients with bicuspid aortic valve (Haunschild et al., 2019). Deletion of Adam17 (MMP) caused aberrant compartmentalization of versican and increased deposition of collagen, affecting postnatal viability (Wilson et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, another histological study reported a higher grade of valvular fibrosis in stenotic BAVs vs. TAVs ( 85 ). On the molecular level, the ECM-degrading protease MMP-2 was shown to have higher expression levels in BAVs than TAVs ( 86 ). Strikingly, in all congenital semilunar valve disease, including BAV, the layered valve microstructure is disrupted ( 87 ).…”
Section: Patterns In the Cellular Contribution Temporal Onset And Risk Factors For Valvular Fibrosismentioning
confidence: 99%